1996
DOI: 10.1021/bi960818q
|View full text |Cite
|
Sign up to set email alerts
|

Localization by Photoaffinity Labeling of Natriuretic Peptide Receptor-A Binding Domain

Abstract: A portion of the ligand binding domain for atrial natriuretic peptide (ANP) was identified as an affinity cross-linked proteolytic fragment of bovine adrenal natriuretic peptide receptor type-A (NPR-A). Affinity purified NPR-A was UV-cross-linked to the amino terminus of 125I-[Tyr2] rat ANP-(2-27). A chymotryptic fragment of the affinity labeled NPR-A was isolated by chromatography and electrophoresis. This fragment yielded a major microsequence corresponding to a region from Met173 to Phe188 of the receptor e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
14
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 39 publications
3
14
0
Order By: Relevance
“…Affinity-labeling experiments indicated that residues 4 and 18 of ANP bind in the vicinity of Met-173 of NPR-A and that the C terminus of ANP binds near His-195. The assignment of receptor contact residues by the crystallography group is consistent with a previous report demonstrating that the amino portion of ANP could be cross-linked to the NPR-A chymotryptic peptide Met-173 to Phe-188 (20). The structure of an ANP-NPR-A complex has not been solved, but van den Akker et al (19) speculate that the dimeric receptor contains two spatially separated ANP-binding sites, which yields a ligand-receptor stoichiometry of 2:2.…”
supporting
confidence: 88%
“…Affinity-labeling experiments indicated that residues 4 and 18 of ANP bind in the vicinity of Met-173 of NPR-A and that the C terminus of ANP binds near His-195. The assignment of receptor contact residues by the crystallography group is consistent with a previous report demonstrating that the amino portion of ANP could be cross-linked to the NPR-A chymotryptic peptide Met-173 to Phe-188 (20). The structure of an ANP-NPR-A complex has not been solved, but van den Akker et al (19) speculate that the dimeric receptor contains two spatially separated ANP-binding sites, which yields a ligand-receptor stoichiometry of 2:2.…”
supporting
confidence: 88%
“…1). Prediction of the localization of the ANP binding region on this receptor was helped by our previous photoaffinity tagging results (22) and was confirmed by site-directed mutagenesis (21). However the predicted localization of the ANP binding site in the V-shaped dimer was more on the lateral face of each receptor subunit in a position not easily amenable to simultaneous contact of the peptide with both receptor subunits or to any conformational change in the receptor (21).…”
mentioning
confidence: 69%
“…Recent mapping of the disulfide bonding pattern of this receptor demonstrates that the first two Cys and second two Cys residues (from the amino terminus) form internal disulfide bonds (29,30). The site of ANP binding has been mapped just to the amino-terminal side of the second disulfide loop (31), suggesting that this region is critical for ligand binding. Limited sequence information from genomic clones of GC-G also demonstrates that intron/exon boundaries are at the same positions in the GC-G gene as in the GC-A and the ANP clearance receptor genes (32,33).…”
Section: Resultsmentioning
confidence: 99%